A Survey Of The Agricultural Economy Of Trengganu 1930 – 1940 - Muda, Mohd. Ali (Universiti Sains Malaysia, 1974)
Trengganu, though under Siamese Influence before the Aglo-Siamese Traty of March 10th 1909, remained very much an independent Malay state due to the stubborn resistance of her ruler and her geographical isolation. Acknowledgement of the Siamese suzerainty was limited to a triennial tribute of the Bunga Mas.